Evaluation of the thermal performance of an innovative prefabricated natural plant fibre building system. (November 2013) - Shea, Andy; Wall, Katharine; Walker, Pete
Energy efficient new and retrofit building construction relies heavily on the use of thermal insulation. A focus on the environmental performance of current construction materials with regards to both embodied energy and energy in-use has resulted in a growing interest in the use of natural fibre insulation materials. The results of heat flow meter thermal conductivity tests on a range of straw samples of different densities are presented. The innovative use of straw in the development of a prefabricated straw-bale panel and the results of guarded hot-box testing are presented. In common with most building materials, there is a degree of uncertainty in the thermal conductivity due to the influences of temperature, moisture content and density; however, from evaluation of a range of the literature and experimental data, a value of 0.064 W/m·K is proposed as a representative design value for straw bales at the densities used in building construction. Computer simulation and experimental testing suggest that the overall heat transfer coefficient ( U -value) for the complete prefabricated panel is approximately 0.178 W/m 2 ·K. This article also briefly discusses the use of this innovative unit in a highly instrumented test building constructed at the University of Bath. Practical application : Knowledge of the thermal properties of building materials is necessary for evaluation of energy performance of the building envelope and appraisal of retrofit fabric improvements. The presentation of robust data for the thermal properties of straw will be of interest to designers developing projects employing this natural fibre insulation material.